2022
DOI: 10.1002/ctd2.134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adipose‐derived exosome and exosomal miRNA on glycolipid metabolism

Abstract: Exosomes secreted by adipose tissue transfer miRNAs to insulin target tissues to regulate glycolipid metabolism. • MiRNAs have emerged as key factors of metabolic homeostasis via regulation of insulin signaling, lipolysis, and inflammation. • MiRNAs dysregulation in metabolic diseases, such as obesity, type 2 diabetes stresses their potential as therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 219 publications
(271 reference statements)
0
2
0
Order By: Relevance
“…3 Interestingly, intercellular communication via EV-associated miRNAs is dysregulated in some pathologies such as metabolic disorders involving various tissues including liver or adipose tissue (AT). [4][5][6][7] In the present review, we have focused our attention on the functions of adipose tissue EV (ADEV)-derived miRNAs in different aspects of metabolic disorders such as type 2 diabetes (T2D) and obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Interestingly, intercellular communication via EV-associated miRNAs is dysregulated in some pathologies such as metabolic disorders involving various tissues including liver or adipose tissue (AT). [4][5][6][7] In the present review, we have focused our attention on the functions of adipose tissue EV (ADEV)-derived miRNAs in different aspects of metabolic disorders such as type 2 diabetes (T2D) and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Among the biological signals, it has been shown that micro‐RNAs (miRNAs) are loaded into various EVs that convey miRNAs from their donor cells to the target cells in order to regulate gene expression 3 . Interestingly, intercellular communication via EV‐associated miRNAs is dysregulated in some pathologies such as metabolic disorders involving various tissues including liver or adipose tissue (AT) 4–7 . In the present review, we have focused our attention on the functions of adipose tissue EV (ADEV)‐derived miRNAs in different aspects of metabolic disorders such as type 2 diabetes (T2D) and obesity.…”
Section: Introductionmentioning
confidence: 99%